Infant feeding and HIV - Ameena Ebrahim Goga (Southern African Journal of HIV Medicine, 2009)
Recent studies on antiretroviral prophylaxis during breastfeeding show that maternal HAART (alone or with 1,4 or 24 weeks infant prophylaxis) or infant prophylaxis alone (with limited maternal prophylaxis) for 6, 14 or 24 weeks reduces HIV transmission through breastmilk (postnatal transmission). Maternal postnatal regimens appear to be as efficacious as infant postnatal regimens, although one study shows a trend favouring infant nevirapine over maternal HAART (both used from 1 week to 6 months post-delivery). These new findings necessitate a review of existing PMTCT interventions, and the immediate implementation of regimens that reduce postnatal transmission - where this is feasible – to save children’s lives. In the public sector, whilst stakeholders engage in discussions about which is the best regimen to minimise postnatal transmission SSSUPPORT should be given to all HIV-positive women, as explained below, to improve infant outcomes and reduce postnatal transmission: Screen all women for HIV, Send off CD4 cell counts on all HIV-positive women, Screen all HIV-positive women for AFASS using a standardised tool (e.g. Table 3); Understand the woman’s personal and socio-cultural context; Promote exclusive or predominant breastfeeding if all AFASS criteria are not met; Promote exclusive formula feeding if all AFASS criteria are met; Organise supplies of formula milk and cotrimoxazole; Review mothers and infants in the first 3 days post-delivery, in the first two weeks postnatally and monthly thereafter, and review health and feeding practices, regardless of feeding choice, at every visit; lastly Treat all pregnant women with HAART if they meet national criteria for HAART initiation.